Соматикалық фразеологизмлер– лингвокультурологиялық бирликлерден бири (SCIENCE and SOCIETY, 2023)
The article analyzes somatic phraseology in the Karakalpak language. It has been scientifically proven that etalon, linguoculturemes, metaphors and phraseological units are linguoculturological units. Scientific conclusions about the linguistic functions of phraseological units are given. Ádebiyattanıw